Penyuluhan Pengolahan Inovasi Makanan Sehat Berbasis Bahan Alam Lokal untuk Anak Usia Dini - Noviasari Handayani; Gunarmi Gunarmi; Selasih Putri Isnawati Hadi (Universitas Sumatera Barat, 2024)
Early childhood according to Law no. 20 of 2003 are children aged 0-6 years. Early childhood growth is very dependent on the child's health which is influenced by the healthy food consumed. Early childhood health problems caused by malnutrition result in stunted growth. This service aims to increase mothers' knowledge about healthy food and improve their skills in processing food innovations based on local natural ingredients for early childhood. This community service was carried out in Sumurejo Village, Gunungpati District, Semarang City, with the target being 18 families in Dawis Amarilis, Sumurejo District. The method used is lecture and demonstration, there is a pre-test and post-test to determine the mother's level of knowledge regarding the material presented. The stages of this activity are carried out starting with needs analysis, preparing permits, preparing materials, implementation starts with giving a pre-test, presenting material and giving a post-test, analyzing the results of community service and ending with reporting. The results of this community service activity can increase mothers' knowledge and skills in processing innovative healthy foods based on local food ingredients. This counseling can be continued regularly to increase mothers' knowledge regarding healthy food innovations based on local natural ingredients for early childhood.